Evaluation Of Medicine Storage Management and Compatibility With Storage Standards in The Pharmaceutical Warehouse of Hospital Badung Regency - Giwangkara, I Gusti Agung Ayu Ningrat; Dewi, Dewa Ayu Putu Satrya; Mayun, I Gusti Ngurah; Suryaningsih, Ni Putu Aryati (Universitas Muhammadiyah Surakarta, 2023)
The effectiveness of drug storage is essential for effective drug management; if it is inadequate, pharmacy services and performance will be compromised. Therefore, a review of drug storage management and the appropriateness of drug storage regulations is required. The purpose of this study was to evaluate the effectiveness of drug storage and the acceptability of drug storage in the pharmaceutical warehouse of Hospital, Badung Regency. This study used cross-sectional methodology, descriptive observational quantitative research, and data collected from all medicinal products between March and April 2023. A checklist taken from the 2010 Binfar guidelines became the research tool. The result Indicators of drug storage such as percentage of matched drugs with stock cards was 100%, percentage of expired drugs was 1,46%, percentage of empty stock was 0%. Result of standards of drug storage such as space organized, drug supplies were prepared, and storage facilities were used was 100%. The results of the suitability of drug storage facilities in the Pharmacy Warehouse of Regional Hospital Badung Regency are in accordance with the standards of drug storage facilities, while the results of the efficiency value of drug storage in the Pharmacy Warehouse of Regional Hospital Badung Regency show that it has not achieved maximum results. Evaluation of drug storage management in the Pharmacy Warehouse of Regency Hospital Badung needs to be carried out regularly to prevent expired drugs and ensure drug supplies are maintained.